-49-6m=5+10(1-7m)

Simple and best practice solution for -49-6m=5+10(1-7m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -49-6m=5+10(1-7m) equation:


Simplifying
-49 + -6m = 5 + 10(1 + -7m)
-49 + -6m = 5 + (1 * 10 + -7m * 10)
-49 + -6m = 5 + (10 + -70m)

Combine like terms: 5 + 10 = 15
-49 + -6m = 15 + -70m

Solving
-49 + -6m = 15 + -70m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '70m' to each side of the equation.
-49 + -6m + 70m = 15 + -70m + 70m

Combine like terms: -6m + 70m = 64m
-49 + 64m = 15 + -70m + 70m

Combine like terms: -70m + 70m = 0
-49 + 64m = 15 + 0
-49 + 64m = 15

Add '49' to each side of the equation.
-49 + 49 + 64m = 15 + 49

Combine like terms: -49 + 49 = 0
0 + 64m = 15 + 49
64m = 15 + 49

Combine like terms: 15 + 49 = 64
64m = 64

Divide each side by '64'.
m = 1

Simplifying
m = 1

See similar equations:

| 2x+18+3x-18=55 | | 4a-8=4-6a | | 17.3=3.2+x | | X+8=28-3x | | (5y+1)(2y-7)= | | -42=7-7x | | 5g+3=2g+9 | | 2(2x-70)=-(3x-35) | | -9x-45=-3x+87 | | 1=x(1-1.1) | | 3+x*4=-x*8 | | 4x^2+32x+1044=0 | | x^2+16x+10=7x-4 | | 32=x+x+5 | | 8j+4j=9j-6 | | 6x-108=126-7x | | x^2+x-2+x-2=x-9+x-9 | | 5=1+p | | (3-4a)(7-5a)= | | 2.25x+1.25t=13.50 | | 4(2)(g)+4(9)30=109 | | 5-2[6-(8y-2)]= | | -12+9x=7x+18 | | 2x+3-4X+1=6 | | 9y-2(3y-30)=y+80 | | 38+2a+54= | | 2(x+50)-6=4(3x+20) | | 18-25n=10 | | 41000000+b=56000000 | | 5-2x=19-5x | | 2x-4=2x+-2 | | x^2+(x-2)(x-2)=(x-9)(x-9) |

Equations solver categories